Fifteen‐Year Trends in Management and Outcomes of Non–ST‐Segment–Elevation Myocardial Infarction Among Black and White Patients: The ARIC Community Surveillance Study, 2000–2014. Issue 19 (2nd October 2018) - Arora, Sameer; Stouffer, George A.; Kucharska‐Newton, Anna; Vaduganathan, Muthiah; Qamar, Arman; Matsushita, Kunihiro; Kolte, Dhaval; Reynolds, Harmony R.; Bangalore, Sripal; Rosamond, Wayne D.; Bhatt, Deepak L.; Caughey, Melissa C.
Abstract : Background: Standardization of evidence‐based medical therapies has improved outcomes for patients with non–ST‐segment–elevation myocardial infarction (NSTEMI). Although racial differences in NSTEMI management have previously been reported, it is uncertain whether these differences have been ameliorated over time. Methods and Results: The ARIC (Atherosclerosis Risk in Communities) Community Surveillance study conducts hospital surveillance of acute myocardial infarction in 4 US communities. NSTEMI was classified by physician review, using a validated algorithm. From 2000 to 2014, 17 755 weighted hospitalizations for NSTEMI (patient race: 36% black, 64% white) were sampled by ARIC. Black patients were younger (aged 60 versus 66 years), more often female (45% versus 38%), and less likely to have medical insurance (88% versus 93%) but had more comorbidities. Black patients were less often administered aspirin (85% versus 92%), other antiplatelet therapy (45% versus 60%), β‐blockers (85% versus 88%), and lipid‐lowering medications (68% versus 76%). After adjustments, black patients had a 24% lower probability of receiving nonaspirin antiplatelets (relative risk: 0.76; 95% confidence interval, 0.71–0.81), a 29% lower probability of angiography (relative risk: 0.71; 95% confidence interval, 0.67–0.76), and a 45% lower probability of revascularization (relative risk: 0.55; 95% confidence interval, 0.50–0.60). No suggestion of a changing trend over time was observed for any NSTEMI therapy ( P values for interaction, all >0.20). Conclusions: This longitudinal community surveillance of hospitalized NSTEMI patients suggests black patients have more comorbidities and less likelihood of receiving guideline‐based NSTEMI therapies, and these findings persisted across the 15‐year period. Focused efforts to reduce comorbidity burden and to more consistently implement guideline‐directed treatments in this high‐risk population are warranted.